Surveillance of RNase P, PMMoV, and CrAssphage in wastewater as indicators of human fecal concentration across urban sewer neighborhoods, Kentucky. (29th January 2022) - Holm, R H; Nagarkar, M; Yeager, R A; Talley, D; Chaney, A C; Rai, J P; Mukherjee, A; Rai, S N; Bhatnagar, A; Smith, T
Abstract: Wastewater surveillance has been widely used as a supplemental method to track the community infection levels of severe acute respiratory syndrome coronavirus 2. A gap exists in standardized reporting for fecal indicator concentrations, which can be used to calibrate the primary outcome concentrations from wastewater monitoring for use in epidemiological models. To address this, measurements of fecal indicator concentration among wastewater samples collected from sewers and treatment centers in four counties of Kentucky (N = 650) were examined. Results from the untransformed wastewater data over 4 months of sampling indicated that the fecal indicator concentration of human ribonuclease P (RNase P) ranged from 5.1 × 10 1 to 1.15 × 10 6 copies/ml, pepper mild mottle virus (PMMoV) ranged from 7.23 × 10 3 to 3.53 × 10 7 copies/ml, and cross-assembly phage (CrAssphage) ranged from 9.69 × 10 3  to 1.85 × 10 8  copies/ml. The results showed both regional and temporal variability. If fecal indicators are used as normalization factors, knowing the daily sewer system flow of the sample location may matter more than rainfall. RNase P, while it may be suitable as an internal amplification and sample adequacy control, has less utility than PMMoV and CrAssphage as a fecal indicator in wastewater samples when working at different sizes of catchment area. The choice of fecal indicator will impact the results of surveillance studies using this indicator to represent fecal load. Our results contribute broadly to an applicable standard normalization factor and assist in interpreting wastewater data in epidemiological modeling and monitoring. Abstract : Review of fecal indicators to foster a wider understanding of factors influencing wastewater results used in epidemiological modeling for public health surveillance.